A Systematic Review of Academic Buoyancy in Adolescents: Psychological and Environmental Predictors of Educational Resilience - Onny Dwi Puspita Sari; Anna Armeini Rangkuti; Deasyanti Deasyanti (STAI Hubbulwathan Duri, 2025)
Academic buoyancy refers to adolescents’ capacity to cope with and rebound from everyday academic setbacks. This study systematically reviews recent evidence on academic buoyancy and its psychological and environmental predictors. Using the PRISMA protocol, we searched peer-reviewed studies in Scopus, ScienceDirect, PubMed, and Google Scholar published in English between 2019 and 2023. Eligible articles reported quantitative findings on academic buoyancy among adolescents. After screening and full-text assessment, 17 studies were included and synthesized using thematic analysis. Across studies, academic buoyancy was consistently associated with both internal and external predictors. Key psychological predictors included self-compassion, academic self-efficacy, achievement goal orientation, and academic motivation. Environmental predictors included perceived support from teachers and parents, positive school climate, and supportive peer relationships. Several studies also positioned academic buoyancy as a mediating mechanism linking psychosocial resources (e.g., support and motivation) to academic outcomes such as engagement and achievement. Overall, the evidence suggests that academic buoyancy functions as a protective and promotive factor for adolescents’ academic well-being and performance. However, the literature is dominated by cross-sectional, self-report designs, limiting causal inference and developmental conclusions. Future research should employ longitudinal and intervention-based approaches, examine cultural and contextual variation, and strengthen measurement across diverse adolescent populations. A limitation of this review is the restriction to four databases and English-language publications only.